Global small-angle X-ray scattering data analysis for multilamellar vesicles: the evolution of the scattering density profile model - Heftberger, Peter (International Union of Crystallography, 2013)
The high-resolution scattering length density analysis method has been generalized from unilamellar to multilamellar lipid vesicles. The method may be applied to X-ray data only, or to a joint analysis of X-ray and neutron data, yielding an improved refinement of the lipid backbone position.